Risk-Based Business Licensing According Perspective of Investment Certainty in Indonesia - Mirozul, Aldy; Wati, Diani Sadia; Meliala, Aurora Jelinia (PT. Riset Press International, 2025)
In order to improve the investment ecosystem and business activities to create jobs, the Government has enacted Law Number 11 of 2020 concerning Job Creation, regulating the simplification of business licensing through the implementation of Risk-Based Business Licensing using standard methods based on risk levels as stated in Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing, the licensing transformation aims to provide legal certainty for foreign investors in investing in Indonesia. This study will examine the implementation of risk-based business licensing based on Government Regulation Number 5 of 2021 using Normative Legal Research or library research, with a statute approach, conceptual approach and historical approach to examine existing legal problems. The results of this study show that the change in business licensing to risk-based business licensing that integrates the authority and licensing issuance process in the OSS system still has problems starting from the implementation of authority and the issuance process of basic requirements, business licensing, supporting business licensing and risk classification based on sector. With these problems still existing, it can create legal certainty for investors to invest in Indonesia so that it is necessary to amend Government Regulation Number 5 of 2021 concerning the Implementation of Risk-Based Business Licensing.